Tethered aminohydroxylation route to L-arabino-[2R,3S,4R] and L-xylo-[2R,3S,4S]-C-18-phytosphingosines - Dubey, Abhishek; Kumar, Pradeep (Tetrahedron Letters, 2009)
A concise and highly efficient synthesis of L-arabino-[2R,3S,4R] and L-xylo-[ 2R,3S,4S]-C-18-phytosphingosines has been achieved. The synthetic strategy features the Sharpless kinetic resolution and tethered aminohydroxylation as the key steps. (C) 2009 Elsevier Ltd, All rights reserved.
Keywords: Phytosphingosine; Regioselectivity; Sharpless asymmetric kinetic resolution; Sphingolipids; stereoselectivity; Tethered aminohydroxylation